2000
DOI: 10.1074/jbc.m001273200
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Insulin-like Growth Factor II/Mannose 6-Phosphate Receptor

Abstract: The insulin-like growth factor II/mannose 6-phosphate receptor (IGF2R) interacts with lysosomal enzymes through two binding domains in its extracytoplasmic domain. We report in the accompanying article (Byrd, J. C., and MacDonald, R. G. (2000) J. Biol. Chem. 275, 18638 -18646) that only one of the two extracytoplasmic mannose 6-phosphate (Man-6-P) binding domains is necessary for high affinity Man-6-P ligand binding, suggesting that, like the cation-dependent Man-6-P receptor, oligomerization of the IGF2R cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
4
52
0
1
Order By: Relevance
“…First, only one of the two extracytoplasmic Man-6-P binding domains is required for the formation of high affinity, strongly supporting the hypothesis that receptor oligomerization is responsible for the ability of multivalent ligands to interact with the receptor with high affinity. In addition, our laboratory has recently found that the IGF2R is capable of forming dimers (49). Second, regions of the IGF2R outside of the minimal Man-6-P binding domain play a role in the formation of high affinity sites.…”
Section: Fig 4 Schematic Diagram and Expression Of Truncated Man-6-mentioning
confidence: 99%
“…First, only one of the two extracytoplasmic Man-6-P binding domains is required for the formation of high affinity, strongly supporting the hypothesis that receptor oligomerization is responsible for the ability of multivalent ligands to interact with the receptor with high affinity. In addition, our laboratory has recently found that the IGF2R is capable of forming dimers (49). Second, regions of the IGF2R outside of the minimal Man-6-P binding domain play a role in the formation of high affinity sites.…”
Section: Fig 4 Schematic Diagram and Expression Of Truncated Man-6-mentioning
confidence: 99%
“…Approximately 90% of membrane-bound IGF-IIR is normally found within the cell. The remaining protein is present at the cell surface, where its extracellular domains can exist as monomers or dimers (7,8). A 23-amino acid transmembrane domain and a cytoplasmic tail containing recognition sequences ensure rapid internalization at the plasma membrane (9).…”
mentioning
confidence: 99%
“…Transient expression of the minireceptors by calcium phosphatemediated transfection into 293T human embryonic kidney cells and immunoblot analysis of cell lysates to measure expression of each construct were also performed as described (37,43).…”
Section: Methodsmentioning
confidence: 99%
“…Radiolabeled pentamannose phosphate-bovine serum albumin (PMP-BSA) and unlabeled PMP-BSA were prepared as described previously (22,37). PMP-Sepharose was prepared as previously described (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation